Cultured microbes represent a substantial fraction of the human and mouse gut microbiota. (3rd September 2017) - Lagkouvardos, Ilias; Overmann, Jörg; Clavel, Thomas
ABSTRACT: During the last 15 years, molecular techniques have been preferred over culture-based approaches for the study of mammalian gut microbiota, i.e. the communities of microorganisms dwelling in the intestine of mammals. The main reason is the belief that the majority of gut bacteria, especially strict anaerobes, escape cultivation. Despite numerous such statements in publications, the literature does not provide a clear overview on the subject. In the present manuscript, we highlight recent work on the cultivation of bacteria from the intestine of mammals, review the literature and provide novel data pertaining to cultured fractions of mammalian gut microbiota. These data show that, despite marked inter-sample variations, 35 to 65% of molecular species detected by sequencing have representative strains in culture.